2019
DOI: 10.1039/c9py01413f
|View full text |Cite
|
Sign up to set email alerts
|

Melamine-mediated supramolecular assembly of nucleobase-modified poly(l-lysine)

Abstract: Melamine (M) was used to drive the supramolecular assembly of thymine (T)-modified poly(l-lysine) into fibers or spherical micelles through simply adjusting the substitution degree of T and the concentration of M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…However, nucleobase-containing polypeptides have been also reported to form supramolecular assemblies that are potentially useful as novel biocompatible and biodegradable materials [122][123][124]. Recently, a nucleobasemodified polylysine was designed and synthesized by the polymerization of lysine and successive modification with thymines [125]. The self-assembly of the nucleobase-containing polypeptide chains was driven by melamine molecules containing three thymine-like faces.…”
Section: Self-assembling Nucleopeptides and Pnas In Biomedicinementioning
confidence: 99%
“…However, nucleobase-containing polypeptides have been also reported to form supramolecular assemblies that are potentially useful as novel biocompatible and biodegradable materials [122][123][124]. Recently, a nucleobasemodified polylysine was designed and synthesized by the polymerization of lysine and successive modification with thymines [125]. The self-assembly of the nucleobase-containing polypeptide chains was driven by melamine molecules containing three thymine-like faces.…”
Section: Self-assembling Nucleopeptides and Pnas In Biomedicinementioning
confidence: 99%
“…For example, cyanuric acid and barbituric acid derivatives promote the formation of rosette-like selfassemblies of molecules with melamine groups, 75 and of melamine-chaperoned molecular assemblies of thyminemodified polypeptides. 76 Li et al reported another approach to fabricate the porous materials composed of cucurbit [8]uril, which involves the use of a combination of cucurbit [8]uril and its guest molecules. 77 The encapsulation improved the solubility of the inclusion complexes in water.…”
Section: Artificial Chaperone Systems Formentioning
confidence: 99%
“…At the same time, Liu et al demonstrated that the addition of l - or d -amino acids into a nongelator induced supramolecular gel formation. , Additionally, artificial chaperone systems for the formation of various molecular assemblies have been reported. For example, cyanuric acid and barbituric acid derivatives promote the formation of rosette-like self-assemblies of molecules with melamine groups, and of melamine-chaperoned molecular assemblies of thymine-modified polypeptides . Li et al reported another approach to fabricate the porous materials composed of cucurbit[8]­uril, which involves the use of a combination of cucurbit[8]­uril and its guest molecules .…”
Section: Artificial Chaperone Systems For Synthetic Moleculesmentioning
confidence: 99%